Factores psociosociales que influyen en los trastornos depresivos de los adultos mayores que asisten al centro gerontológico municipal San Ignacio del cantón Huaquillas en el año 2013. - Ascencio Cabanilla, Sonia Magali (2013)
The research process led to the conclusion that inadequate family relationships and lack of social support and attention to the needs of occupational health and, significantly influence the development of disorders in the elderly who attend the Municipal Gerontology Program San Ignacio Canton Huaquillas year 2013.